IMPACT OF BEHAVIORAL BIASES ON INDIVIDUAL’S RETIREMENT PLANNING IN PAKISTAN - Zil-e-Huma Najeeb; Dr. Farman Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the effect of affective, cognitive and conative biases on the individual’s retirement planning. The data was collected from fifty eight private sector universities of major cities of Pakistan with the help of adapted questionnaire. The sampling used here is stratified random sampling because the data was collected from five major cities of Pakistan considering each city as strata. The findings of this study support the social cognitive theory and show highly significant and positive effect of behavioral biases on the individuals planning for their old age.